Social Intelligence as a Factor of Volunteer Activities by Future Medical Workers - Onufriieva, Liana; Chaikovska, Oksana; Kobets, Oleksandr; Pavelkiv, Roman; Melnychuk, Tetiana (Journal of History Culture and Art Research, 2020)
The article presents the results of theoretical and empirical studies of social intelligence of students of a medical College in the implementation of socially useful activities by means of volunteer work. Social intelligence is considered as a relatively stable system of intellectual abilities, which are expressed in social behavior of the individual. The author highlighted the role of social intelligence in the activities of future health professionals. The article analyzes psychological studies on the problem of social intelligence. During the empirical study revealed the level of social intelligence of students-volunteers, established its relationship with the level of empathic tendencies and the type of interpersonal relations. It is noted that the formation of social intelligence defines social perception, social sensitivity, social thinking, reflection and empathy. Social intelligence is the ability to develop in social interaction. The level of development of social intelligence in General and its individual abilities associated with the personal characteristics and features identify companies. Found that social intelligence is part of the communicative-reflective component of psychological readiness of students to volunteer activities, include the appropriate communicative competence as the ability to formulate their opinions and to understand the other person’s opinion, the ability to recognize both verbal and nonverbal cues in the communication process, accounting for age and individual aspects of communication, availability of appropriate perceptual mechanisms (empathy, reflection, identification), the ability to interact with colleagues and people assisted, ability to work in a team and find a way out of conflict situations and etc. It is concluded that the development of social intelligence of future specialists due to empathic tendencies, the prevailing structure of values, respect for others, their behavior and actions, types of interpersonal relations. The identified level of social intelligence of students and volunteers, its relationship with the level of empathic tendencies and the type of interpersonal relations indicates the need to develop experimental psychological program of formation of social intelligence in future medical professionals.